High-porosity corrosion-resistant fiber membrane with armored structure as well as preparation method and application of high-porosity corrosion-resistant fiber membrane
By uniformly encapsulating conjugated microporous polymer on the polylactic acid nanofiber membrane, a high pore corrosion-resistant fiber membrane was prepared, which solved the problem of inefficiency of synchronous filtration materials of dust and toxic gases in the prior art, and achieved efficient dust filtration and gas adsorption.
Patent Information
- Application Number
- CN202411985313.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The dust filtration efficiency of existing dust and toxic gas synchronous filtering materials is low, and the gas adsorption capacity is low, making it difficult to effectively remove toxic gases such as hydrogen sulfide.
Polylactic acid nanofiber membranes were used as solid templates to induce conjugated microporous polymers to uniformly encapsulate the fiber surface through molecular-level interactions to prepare a fiber membrane with high pore corrosion resistance. The fiber membrane has a fiber armored structure, which enhances its pore properties and acid, alkali and corrosion resistance.
It has achieved efficient synchronous filtration and removal of dust and toxic gases. The fiber membrane has a large specific surface area, uniform pore distribution, strong corrosion resistance, dust filtration efficiency is as high as more than 96.8%, and the H2S adsorption volume is higher than 4.9 mmol/g.
Smart Images

Figure CN119663540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of controllable synthesis induced by using fiber membrane as template, and in particular to a high-porosity corrosion-resistant fiber membrane for synchronously filtering out dust and poisonous gas, and a preparation method and application thereof. Background Art
[0002] Hydrogen sulfide (H2S) is a colorless, highly toxic acidic gas with the smell of rotten eggs. It is commonly found in natural gas and biogas. Due to its extremely strong toxicity, even low concentrations of H2S can have serious impacts on human health and the atmospheric environment. Various methods have been explored to reduce H2S emissions, including absorption, adsorption technology, membrane separation, catalytic oxidation, etc. However, due to the limitations of the acidic characteristics of H2S gas, strict requirements are placed on the porosity and physicochemical properties of the materials used. Although H2S is harmful to the human body, it is also a valuable resource that can be recovered and converted into high-value products such as sulfur and mercaptans. At the same time, most of the H2S gas streams emitted inevitably carry harmful particles such as dust, which increases the difficulty of simultaneous filtration. Therefore, for environmental and economic reasons, it is particularly important to develop dust and toxic gas simultaneous filtration materials with high porosity and corrosion resistance.
[0003] In recent decades, researchers have been studying various materials for H2S removal, including metal-organic frameworks (MOFs) and metal-free adsorbents (porous carbon materials, covalent organic frameworks (COFs), and covalent organic polymers (COPs)). However, these adsorbents have certain limitations that hinder their practical application. For example, MOFs contain a large number of unsaturated metal sites, are structurally unstable, and are easily affected by acidic environments, resulting in structural collapse and deformation, which significantly reduces the adsorption capacity and cycle life. The preparation of carbon materials usually requires high-temperature calcination, which is energy-consuming and complex, and has low sulfur adsorption and insufficient active sites. In addition, COFs and COPs also have problems such as high ligand cost, complex synthesis process, and poor H2S adsorption capacity. These inherent disadvantages greatly limit their practical application. Therefore, it is urgent to design new adsorbents with low cost, simple operation, and strong H2S adsorption capacity to overcome these limitations.
[0004] The synthesis and application of polymer nanocomposites have attracted the attention of many researchers and are currently in a stage of rapid innovation and development. As a key component of composite materials, polymer nanofibers have various preparation methods, including template synthesis, self-assembly, phase separation, etc. However, these methods have limitations such as complex process, high cost, and limited output. In contrast, spinning, as an important preparation method, has significant advantages such as mature process, continuous production, and easy scale-up. It can efficiently prepare high-quality polymer nanofibers to meet the growing demand for nanofiber materials in different fields. Conjugated microporous polymers (CMPs) are a class of organic porous polymers with π-conjugated frameworks and permanent microporous structures, which are formed by organic structural units connected by covalent bonds. As a porous organic polymer (POPs) material, CMPs have large specific surface area, adjustable pores, controllable composition and structure, and moisture and acid and alkali resistance. In situ growth of CMPs on degradable polylactic acid spinning membranes can significantly enhance the physical and chemical stability and porous properties of the fiber membranes, and is expected to improve dust filtration efficiency and gas adsorption capacity while combining the low gas permeation resistance of nanofiber membranes. Summary of the invention
[0005] The main purpose of the present invention is to prepare a fiber membrane with rich porosity and acid, alkali and corrosion resistance that can simultaneously filter out dust and toxic gases, so as to solve the problems of low dust filtration efficiency and low gas adsorption capacity of existing gas purification materials that simultaneously filter out dust and toxic gases.
[0006] In order to achieve the above-mentioned purpose, the present invention provides a fiber membrane with a high porosity and corrosion-resistant armored structure and a preparation method and application thereof. According to the first aspect of the present invention, a preparation method of a fiber membrane with a high porosity and corrosion-resistant armored structure is provided, comprising the following steps: Step S1, preparation of polylactic acid spinning stock solution: polylactic acid (PLA) is uniformly dispersed in an organic solvent to prepare a polylactic acid spinning stock solution; Step S2, preparation of polylactic acid nanofiber membrane: the polylactic acid spinning stock solution obtained in step S1 is used to prepare a polylactic acid nanofiber membrane by spinning technology; Step S3, preparation of a conjugated microporous polymer precursor solution: bromine monomer, alkyne monomer, and catalyst are fully dissolved in a reaction solvent to prepare a conjugated microporous polymer precursor solution; Step S4, preparation of a high porosity and corrosion-resistant fiber membrane: the polylactic acid nanofiber membrane obtained in step S2 is used as a solid template, placed in the conjugated microporous polymer precursor solution obtained in step S3, and a coupling reaction occurs in an inert gas atmosphere to prepare a high porosity and corrosion-resistant fiber membrane with a fiber armored structure.
[0007] Preferably, the organic solvent in step S1 is one or more of dichloromethane, chloroform, chloroform, acetone, ethyl acetate, N,N-dimethylformamide, methanol, ethanol, toluene, and triethylamine, and the concentration of polylactic acid in the polylactic acid spinning solution is 0.5-30 wt%.
[0008] Preferably, the spinning technology in step S2 is one or more of high-voltage electrospinning, high-speed airflow spinning, high-speed centrifugal spinning, and high-temperature melt spinning technology, and the obtained polylactic acid nanofiber membrane has a thickness of 50-150 μm and an average fiber diameter of 50-500 nm.
[0009] Preferably, in step S3, the acetylene monomer is one or more of 1,4-diethynylbenzene, 1,3,5-triethynylbenzene, 1,3,6,8-tetraethynylpyrene, 2,4,6-tri-4-ethynylphenyl-1,3,5-triazine, and tri-4-ethynylphenylamine; the bromine monomer is one or more of 2,6-dibromophenol, tribromophenol, tetrabromophenol, pentabromophenol, 2,6-dibromo-4-methylphenol, bromoxynil, and 4-amino-2,6-dibromophenol, and the functional group molar ratio of the bromine monomer to the acetylene monomer is 5:1‒1:5.
[0010] Preferably, the catalyst in step S3 is a palladium-based catalyst and a copper-based catalyst, the palladium-based catalyst is one or more of palladium acetate, palladium chloride, tetrakistriphenylphosphine palladium, trisdibenzylideneacetone dipalladium, and palladium-carbon catalyst; the copper-based catalyst is one or more of cuprous iodide, cuprous bromide, cupric chloride, copper acetate, copper sulfate, and nano-copper catalyst; the molar ratio of the palladium-based catalyst to the copper-based catalyst is 1:5‒1:20.
[0011] Preferably, the reaction solvent in step S3 is a mixed solution of one of toluene, dichloromethane, chloroform, chloroform, tetrahydrofuran, 1,2-dichloroethane, acetonitrile, dioxane, pyridine, N,N-dimethylformamide and triethylamine, and the volume ratio of the above one substance to triethylamine is 5:1‒1:5.
[0012] Preferably, the inert gas atmosphere in step S4 uses one or more of nitrogen, helium, neon, argon, krypton and xenon, and the purity of the inert gas is maintained above 99.9%.
[0013] Preferably, the coupling reaction in step S4 is a Sonogashira coupling reaction, the reaction temperature is 40-80° C., and the reaction time is 24-72 hours.
[0014] Preferably, the organic solvent in step S1 is selected from N,N-dimethylformamide and dichloromethane in a mass ratio of 3:7.
[0015] In order to achieve the above object, according to the second aspect of the present invention, the present invention also provides a fiber membrane obtained by the above-mentioned preparation method, the fiber membrane having a fiber armor structure (the average fiber diameter is 650‒780nm), a high specific surface area (277 m 2 / g‒324 m 2 / g), small pore size (1.87 nm‒2.29 nm), high dust (PM 0.3 and PM 2.5 The filtration efficiency is higher than 96.8%) and H2S (adsorption capacity is higher than 4.9 mmol / g) are characterized by simultaneous filtration efficiency.
[0016] In order to achieve the above object, according to the third aspect of the present invention, the present invention also provides the use of the above fiber membrane in a filter material for simultaneously filtering out ultrafine dust and toxic gases.
[0017] The beneficial effects of the present invention are as follows: by applying the technical scheme of the present invention, the preparation method of the fiber membrane with high porosity and corrosion-resistant armored structure of the present invention, (1) using polylactic acid nanofiber membrane as a solid template, inducing the uniform and directional encapsulation of conjugated microporous polymer on the fiber surface through molecular level interaction, reducing the disordered stacking and agglomeration of porous polymer; (2) uniformly encapsulating the conjugated microporous polymer on the outer wall of the fiber tube, promoting the fiber membrane to have rich pore properties, while alleviating the problem of poor processability and difficult molding of conjugated microporous polymer, and broadening the application scope and scenarios of the fiber membrane; (3) the rigid conjugated skeleton of the conjugated microporous polymer itself gives the polylactic acid nanofiber membrane excellent acid and alkali corrosion resistance, and the three-dimensional network structure of electrospinning reduces the mass transfer resistance of the airflow, thereby realizing the simultaneous filtration of dust and toxic gases; (4) the various steps work synergistically with each other, not only having excellent pore properties, but also having excellent acid and alkali corrosion resistance, effectively solving the demand for simultaneous filtration of dust and toxic gases, and having broad application potential and market prospects.
[0018] The fiber membrane of the present invention not only has a series of advantages such as large specific surface area, uniform pore distribution, resistance to corrosion and steam erosion, excellent dust filtration performance, and ideal adsorption capacity for toxic gases, but also has a unique fiber armored structure, a simple preparation process, and mild conditions. It is a high-performance, multi-field dust and toxic gas simultaneous filtration gas purification material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 This is a scanning electron microscope image of the high-porosity corrosion-resistant fiber membrane in Example 1.
[0021] Figure 2This is a transmission electron microscope image of the high-porosity corrosion-resistant fiber membrane in Example 1.
[0022] Figure 3 This is the Fourier transform infrared spectrum of the high porosity corrosion-resistant fiber membrane in Example 2.
[0023] Figure 4 This is the powder X-ray diffraction spectrum of the high-porosity corrosion-resistant fiber membrane in Example 3.
[0024] Figure 5 This is the nitrogen adsorption-desorption isotherm curve of the high-porosity corrosion-resistant fiber membrane in Example 4.
[0025] Figure 6 This is a pore size distribution curve of the high-porosity corrosion-resistant fiber membrane in Example 4.
[0026] Figure 7 It is a schematic flow chart of the method of the present invention. DETAILED DESCRIPTION
[0027] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present invention. The present invention will be described in detail below in conjunction with the embodiments.
[0028] like Figure 7As shown, Example 1 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, comprising the following steps: Step S11, preparation of polylactic acid spinning solution: uniformly dispersing polylactic acid (PLA) in a mixed solvent consisting of N,N-dimethylformamide and acetone (mass ratio 4:1) to prepare a polylactic acid spinning solution, wherein the concentration of polylactic acid in the polylactic acid spinning solution is 11 wt%; Step S12, preparation of a polylactic acid nanofiber membrane: the polylactic acid spinning solution obtained in step S11 is subjected to high-voltage electrospinning technology (working voltage of 2-60 kV, spraying speed of 0.5-5 mL / h, receiving distance of 15-25 cm, temperature of 10-50°C, relative humidity of 10-70%, reciprocating speed of 1-5 cm / min) to prepare a polylactic acid nanofiber membrane, wherein the obtained fiber membrane has a thickness of 50-150 μm, and the average diameter of the polylactic acid nanofibers is 50-500 μm. nm; Step S13, preparing a conjugated microporous polymer precursor solution: fully dissolving 2,6-dibromophenol and 1,3,5-triethynylbenzene (functional group molar ratio of 1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 1:10) in a reaction solvent composed of toluene and triethylamine (volume ratio of 1:1) to prepare a conjugated microporous polymer precursor solution; Step S14, preparing a high-porosity corrosion-resistant fiber membrane: using the polylactic acid nanofiber membrane obtained in Step S12 as a solid template, placing it in the conjugated microporous polymer precursor solution obtained in Step S13, replacing the air in the reaction system with nitrogen at room temperature, slowly raising the temperature from room temperature to 50°C, and reacting for 48 hours to prepare a high-porosity corrosion-resistant fiber membrane with a fiber armor structure, the obtained armored fiber has an average diameter of 700nm and a specific surface area of 324 m 2 / g, and the average pore size is 1.87 nm.
[0029] Embodiment 2 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, comprising the following steps: Step S21, preparation of polylactic acid spinning stock solution: uniformly dispersing polylactic acid (PLA) in a mixed solvent consisting of N,N-dimethylformamide and dichloromethane (mass ratio 3:7) to prepare a polylactic acid spinning stock solution, wherein the concentration of polylactic acid in the solution is 9 wt %; Step S22, preparation of a polylactic acid nanofiber membrane: the polylactic acid spinning stock solution obtained in step S21 is subjected to high-speed airflow spinning technology (the injection angle is 15-60°, the ratio of injection speed to extrusion speed is 1k-30k, the injection pressure is 0.2-10 MPa, the airflow temperature is 25-85°C, and the relative humidity is 40-80%) to prepare a polylactic acid nanofiber membrane, wherein the obtained fiber membrane has a thickness of 150 μm and an average diameter of the polylactic acid nanofibers is 400 nm; Step S23, preparing a conjugated microporous polymer precursor solution: fully dissolving tribromophenol and 1,4-diethynylbenzene (functional group molar ratio of 1:3), palladium chloride and cuprous bromide (molar ratio of 1:5) in a reaction solvent composed of dichloromethane and triethylamine (volume ratio of 2:1) to prepare a conjugated microporous polymer precursor solution; Step S24, preparing a high-porosity corrosion-resistant fiber membrane: using the polylactic acid nanofiber membrane obtained in Step S22 as a solid template, placing it in the conjugated microporous polymer precursor solution obtained in Step S23, replacing the air in the reaction system with nitrogen at room temperature, slowly raising the temperature from room temperature to 80°C, and reacting for 24 hours to prepare a high-porosity corrosion-resistant fiber membrane with a fiber armor structure. The obtained armored fiber has an average diameter of 780 nm and a specific surface area of 306 m 2 / g, and the average pore size is 2.11 nm.
[0030] Embodiment 3 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, comprising the following steps: Step S31, preparation of polylactic acid spinning solution: uniformly dispersing polylactic acid (PLA) in a mixed solvent consisting of dichloromethane and N,N-dimethylformamide (mass ratio 7:3) to prepare a polylactic acid spinning solution, wherein the concentration of polylactic acid in the solution is 13 wt%; Step S32, preparation of a polylactic acid nanofiber membrane: the polylactic acid spinning solution obtained in step S31 is subjected to high-speed centrifugal spinning technology (centrifugal speed of 1k-50k, rotation radius of 5-50 cm, solution supply rate of 0.1-10 ml / h, receiving distance of 10-50 cm, ambient temperature of 15-35°C, relative humidity of 30-60%) to prepare a polylactic acid nanofiber membrane, wherein the obtained fiber membrane has a thickness of 50 μm and an average diameter of the polylactic acid nanofibers of 200 nm; Step S33, preparing a conjugated microporous polymer precursor solution: tetrabromophenol and 1,3,6,8-tetraethynylpyrene (functional group molar ratio of 3:1), palladium acetate and copper acetate (molar ratio of 1:15) are fully dissolved in a reaction solvent composed of chloroform and triethylamine (volume ratio of 2:1) to prepare a conjugated microporous polymer precursor solution; Step S34, preparing a high-porosity corrosion-resistant fiber membrane: the polylactic acid nanofiber membrane obtained in step S32 is used as a solid template and placed in the conjugated microporous polymer precursor solution obtained in step S33, and the air in the reaction system is replaced by nitrogen at room temperature, and the temperature is slowly increased from room temperature to 40°C. The reaction time is 72 hours to prepare a high-porosity corrosion-resistant fiber membrane with a fiber armor structure. The obtained armored fiber has an average diameter of 650 nm and a specific surface area of 291 m 2 / g, and the average pore size is 2.17 nm.
[0031] Embodiment 4 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, comprising the following steps: Step S41, preparation of polylactic acid spinning solution: uniformly dispersing polylactic acid (PLA) in a mixed solvent consisting of dichloromethane and acetone (mass ratio 6:4) to prepare a polylactic acid spinning solution, wherein the concentration of polylactic acid in the solution is 11wt%; Step S42, preparation of a polylactic acid nanofiber membrane: the polylactic acid spinning solution obtained in step S41 is subjected to high-temperature melt spinning technology (melting temperature is 100-150°C, heating rate is 5-20°C / min. Pressure control is 1-10 MPa, spinning speed is 500-5000 m / min, traction ratio is 1-10 times, and collection distance is 0.3-1.0 m) to prepare a polylactic acid nanofiber membrane, the obtained fiber membrane has a thickness of 70 μm, and the average diameter of the polylactic acid nanofibers is 280 nm; Step S43, preparing a conjugated microporous polymer precursor solution: pentabromophenol and 1,3,5-triethynylbenzene (functional group molar ratio of 1:2), tridibenzylideneacetone dipalladium and copper sulfate (molar ratio of 1:10) are fully dissolved in a reaction solvent composed of 1,2-dichloroethane and triethylamine (volume ratio of 3:2) to prepare a conjugated microporous polymer precursor solution; Step S44, preparing a high-porosity corrosion-resistant fiber membrane: the polylactic acid nanofiber membrane obtained in step S42 is used as a solid template and placed in the conjugated microporous polymer precursor solution obtained in step S43, and the air in the reaction system is replaced by nitrogen at room temperature, and the temperature is slowly increased from room temperature to 60°C. The reaction time is 48 hours to prepare a high-porosity corrosion-resistant fiber membrane with a fiber armor structure. The obtained armored fiber has an average diameter of 720 nm and a specific surface area of 277 m 2 / g, and the average pore size is 2.29 nm.
[0032] Comparative Example 1 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, and the high porosity and corrosion-resistant fiber membrane is basically prepared by the method of Example 1. The difference is that this example does not use polylactic acid nanofiber membrane as a solid template, and directly synthesizes a conjugated microporous polymer. Specifically, 2,6-dibromophenol and 1,3,5-triethynylbenzene (functional group molar ratio of 1:1), tetrakistriphenylphosphine palladium and cuprous iodide (molar ratio of 1:10) are fully dissolved in a reaction solvent composed of toluene and triethylamine (volume ratio of 1:1) to prepare a conjugated microporous polymer precursor solution; the obtained conjugated microporous polymer precursor solution is replaced with nitrogen at room temperature in the reaction system, and the temperature is slowly increased from room temperature to 50°C. The reaction time is 48 hours to prepare a powder-shaped conjugated microporous polymer with a specific surface area of 57 m 2 / g, and the average pore size is 2.45 nm.
[0033] Comparative Example 2 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, and the method of Example 2 is basically used to prepare a high porosity and corrosion-resistant fiber membrane. The difference is that this example uses a polyvinylidene fluoride nanofiber membrane as a solid template to prepare a high porosity and corrosion-resistant fiber membrane. Specifically, polyvinylidene fluoride (PVDF) is uniformly dispersed in a mixed solvent consisting of N,N-dimethylformamide and dichloromethane (mass ratio 3:1), and the concentration of polylactic acid in the solution is 9 wt% to prepare a polylactic acid spinning solution; the obtained polylactic acid spinning solution is subjected to high-speed airflow spinning technology (the injection angle is 15-60°, the ratio of injection speed to extrusion speed is 1k-30k, the injection pressure is 0.2-10 MPa, the airflow temperature is 25-85°C, and the relative humidity is 40-80%) to prepare a polyvinylidene fluoride nanofiber membrane, and the obtained polylactic acid fiber membrane has a thickness of 150 μm and an average diameter of the nanofibers is 400 nm; tribromophenol and 1,4-diethynylbenzene (functional group molar ratio of 1:3), palladium tetrachloride and cuprous bromide (molar ratio of 1:5) were fully dissolved in a reaction solvent consisting of dichloromethane and triethylamine (volume ratio of 2:1) to prepare a conjugated microporous polymer precursor solution; the obtained polyvinylidene fluoride nanofiber membrane was used as a solid template and placed in the obtained conjugated microporous polymer precursor solution, and the air in the reaction system was replaced by nitrogen at room temperature, and the temperature was slowly increased from room temperature to 80°C. The reaction time was 24 hours to prepare a high-porosity, corrosion-resistant fiber membrane with a fiber armored structure. The obtained fiber had an average diameter of 850 nm and a specific surface area of 91 m 2 / g, and the average pore size is 2.26 nm.
[0034] Comparative Example 3 of the present invention provides a method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, and the method of Example 3 is basically used to prepare a high porosity and corrosion-resistant fiber membrane. The difference is that this example uses a polyaromatic benzene ring monomer to prepare a conjugated microporous polymer shell layer. Specifically, polylactic acid (PLA) is uniformly dispersed in a mixed solvent consisting of dichloromethane / N,N-dimethylformamide (mass ratio 7:3), and the concentration of polylactic acid in the solution is 13 wt%, to prepare a polylactic acid spinning solution; the obtained polylactic acid spinning solution is subjected to high-speed centrifugal rotary spinning technology (centrifugal speed of 1k-50k, rotation radius of 5-50 cm, solution supply rate of 0.1-10 ml / h, receiving distance of 10-50 cm, ambient temperature of 15-35°C, relative humidity of 30-60%) to prepare a polylactic acid nanofiber membrane, and the obtained fiber membrane has a thickness of 50 μm, and the average diameter of the polylactic acid nanofiber is 200 nm; 3,9-dibromoperylene and 1,3,6,8-tetraethynylpyrene (functional group molar ratio of 3:1), palladium acetate and copper acetate (molar ratio of 1:15) were fully dissolved in a reaction solvent consisting of chloroform and triethylamine (volume ratio of 2:1) to prepare a conjugated microporous polymer precursor solution; the obtained polylactic acid nanofiber membrane was used as a solid template and placed in the obtained conjugated microporous polymer precursor solution, and the air in the reaction system was replaced by nitrogen at room temperature, and the temperature was slowly increased from room temperature to 40°C. The reaction time was 72 hours to prepare a high-porosity, corrosion-resistant fiber membrane with a fiber armor structure. The obtained fiber had an average diameter of 680 nm and a specific surface area of 97 m 2 / g, and the average pore size is 2.22 nm.
[0035] The structural characterization and performance testing are shown below.
[0036] Scanning electron microscope observation: The microstructure of the high-porosity corrosion-resistant fiber membrane was observed by field emission scanning electron microscope (model JSM-7900F, Japan Electronics Co., Ltd.) Figure 1 ).
[0037] Transmission electron microscopy observation: The microstructure of the high-porosity corrosion-resistant fiber membrane was observed by field emission transmission electron microscopy (TECNI G2 TF20, FEI Company, the Netherlands). Figure 2 ).
[0038] Functional group structure test: An infrared spectrometer (model VERTEX 70, Bruker, USA) was used to record the functional groups of high porosity and corrosion-resistant fiber membranes ( Figure 3 ).
[0039] Crystal structure test: An X-ray spectrometer (model D / Max-2400, Rigaku Corporation, Japan) was used to record the crystal structure of the high-porosity corrosion-resistant fiber membrane ( Figure 4).
[0040] Specific surface area test: The nitrogen adsorption isotherm of the high porosity and corrosion-resistant fiber membrane was measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA). Figure 5 , Figure 6 ).
[0041] Filtration performance test: The fiber membrane (area 25 cm 2 ) with the gas flow rate set to 85 L / min. At least three different positions were tested for each filter set and the results were averaged.
[0042] Hydrogen sulfide adsorption performance test: H2S was adsorbed using a gas adsorption instrument (ASAP 2020, Micromeritics, USA). High-purity gas H2S (99.999%) was used for adsorption measurements, while free space was measured with helium (99.999%). Isotherm adsorption was performed at 273 K (ice water bath) and 298 K (water bath).
[0043] The experimental results are shown below: Figure 1 The scanning electron microscope image of the high porosity and corrosion-resistant fiber membrane obtained in Example 1 shows that the polylactic acid nanofibers uniformly encapsulate the conjugated microporous polymer shell layer, and the average fiber diameter is 700nm. Due to the guidance of the template effect of the polylactic acid nanofiber membrane, the membrane product of the reverse cross-coupled conjugated microporous polymer presents a nanotube armored morphology and is uniformly encapsulated in the polylactic acid nanofiber tube, proving that the template preparation method can change the microscopic morphology of the conjugated microporous polymer. In addition, it was found in Comparative Example 3 that the type of monomer affects the encapsulation phenomenon on the surface of the conjugated microporous polymer nanotube. It can be clearly seen that a large number of conjugated microporous polymer particles attached to the tube wall are accumulated.
[0044] Figure 2 The transmission electron microscope image of the high porosity and corrosion-resistant fiber membrane in Example 1 shows that the conjugated microporous polymer is evenly wrapped on the surface of the polylactic acid fiber without obvious agglomeration or dissociation. The shell thickness of the conjugated microporous polymer is measured to be in the range of 100-200 nm. In addition, it is found in Comparative Example 3 that the type of monomer affects the encapsulation thickness of the conjugated microporous polymer nanotube surface.
[0045] Figure 3 is the Fourier transform infrared spectrum of the high porosity corrosion-resistant fiber membrane in Example 2, showing that at 3450 cm −1 The peak at 3039 cm-1 demonstrates the stretching vibrations of the O‒H bands associated with intermolecular and intramolecular hydrogen bonding. −1~2834 cm −1 Represents the presence of C-H stretching vibration in the molecular skeleton, 1000-1140 cm −1 The gradually broadening peaks between the two are due to the C‒O vibration of the phenol group. The above results indicate the uniform synthesis of conjugated microporous polymers on polylactic acid nanofibers and the interaction between the two at the molecular level.
[0046] Figure 4 This is the powder X-ray spectrum of the high-porosity corrosion-resistant fiber membrane in Example 3. The spectrum has a broad diffraction peak at 20°. The peak position of the fiber membrane after the conjugated microporous polymer synthesis does not change, indicating that the crystal structure of the membrane has not changed. It is an amorphous polymer similar to the conjugated microporous polymer and has no fixed crystal structure.
[0047] like Figure 5 As shown in the figure, the nitrogen adsorption-desorption isotherm of the high-porosity corrosion-resistant fiber membrane in Example 4 of the present invention shows a mixed curve of type I and type IV isotherms, indicating the presence of micropores and mesopores in the fiber membrane. Figure 6 As shown in the pore size distribution curve of the high-porosity corrosion-resistant fiber membrane in Example 4 of the present invention, the pore size distribution is continuous and consists of a large number of nanopores with a pore size less than 10 nm, corresponding to a microporous structure.
[0048] The adsorption and desorption isotherms showed similar trends, including a medium-pressure region where the nitrogen adsorption amount gradually increased and a high-pressure region where nitrogen was rapidly adsorbed. Combined with the pore size distribution curve, it shows that the monolithic adsorbent has a hierarchical porous structure.
[0049] Table 1 compares the specific surface area, pore size, average fiber diameter, filtration efficiency and hydrogen sulfide adsorption results of the high-porosity corrosion-resistant fiber membranes obtained in the embodiments and comparative examples, as shown in the following table.
[0050] Table 1
[0051]
[0052] Examples 1-4 have a higher specific surface area (277 m 2 / g‒324 m 2 / g) and a smaller pore size (1.87nm‒2.29nm). This is because the polylactic acid nanofibers are used as solid templates to induce the uniform and orderly growth of conjugated microporous polymers on the fibers through molecular level interactions, thereby fully exposing the pore properties of the porous polymers. The specific surface area of comparative example 1 is only 57 m 2 / g, and the average pore size is 2.45 nm. This is because the direct preparation of conjugated microporous polymer without using polylactic acid nanofiber membrane as a solid template leads to disordered growth and partial agglomeration.
[0053] The ability of high-porosity, corrosion-resistant fiber membrane to simultaneously remove dust and toxic gases is closely related to the specific surface area, pore size and film formation. The dust (PM 0.3 and PM 2.5 ) filtration efficiency is above 96.8%, and the adsorption capacity of toxic gas (H2S) is above 4.9 mmol / g, showing good dust and toxic gas simultaneous filtration capabilities. Among them, Example 1 with the highest specific surface area and the smallest pore size performs best in the performance test, PM 0.3 and PM 2.5 The filtration efficiency reaches 99.7% and 99.9% respectively, and the H2S adsorption capacity is 6.1 mmol / g, which is much higher than the comparative examples 1-3 with low specific surface area and large pore size (the H2S adsorption capacity is less than 3.2 mmol / g). The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited to this. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations. In addition, the various different embodiments of the present invention can also be combined arbitrarily, as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure, characterized in that: The following steps are involved: Step S1, dissolving polylactic acid in an organic solvent to obtain a polylactic acid spinning solution; Step S2, processing the polylactic acid spinning solution obtained in step S1 by spinning technology to obtain a polylactic acid nanofiber membrane; Step S3, dissolving the bromine monomer, the alkyne monomer and the catalyst in a reaction solvent to obtain a conjugated microporous polymer precursor solution; Step S4, using the polylactic acid nanofiber membrane obtained in step S2 as a solid template, placing it in the conjugated microporous polymer precursor solution obtained in step S3, and obtaining a high-porosity, corrosion-resistant fiber membrane with a fiber armored structure through a coupling reaction in an inert gas atmosphere.
2. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: In the step S1, the organic solvent is one or more of dichloromethane, chloroform, chloroform, acetone, ethyl acetate, N,N-dimethylformamide, methanol, ethanol, toluene, and triethylamine, and the concentration of the polylactic acid in the polylactic acid spinning solution is 0.5-30wt%.
3. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: The spinning technology in step S2 is one or more of high-voltage electrospinning, high-speed airflow spinning, high-speed centrifugal spinning, and high-temperature melt spinning technology, and the obtained polylactic acid nanofiber membrane has a thickness of 50-150 μm and a fiber diameter of 50-500 nm.
4. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: In step S3, the acetylene monomer is one or more of 1,4-diethynylbenzene, 1,3,5-triethynylbenzene, 1,3,6,8-tetraethynylpyrene, 2,4,6-tri-4-ethynylphenyl-1,3,5-triazine, and tri-4-ethynylphenylamine; the bromine monomer is one or more of 2,6-dibromophenol, tribromophenol, tetrabromophenol, pentabromophenol, 2,6-dibromo-4-methylphenol, bromoxynil, and 4-amino-2,6-dibromophenol; and the functional group molar ratio of the bromine monomer to the acetylene monomer is 5:1-1:
5.
5. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: The catalyst in step S3 is a palladium-based catalyst and a copper-based catalyst, the palladium-based catalyst is one or more of palladium acetate, palladium chloride, tetrakistriphenylphosphine palladium, trisdibenzylideneacetone dipalladium, and palladium-carbon catalyst, the copper-based catalyst is one or more of cuprous iodide, cuprous bromide, cupric chloride, copper acetate, copper sulfate, and nano-copper catalyst, and the molar ratio of the palladium-based catalyst to the copper-based catalyst is 1:5-1:
20.
6. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: The reaction solvent in step S3 is a mixed solution of one of toluene, dichloromethane, chloroform, chloroform, tetrahydrofuran, 1,2-dichloroethane, acetonitrile, dioxane, pyridine, N,N-dimethylformamide and triethylamine, and the volume ratio of the two substances in the mixed solution is 5:1-1:
5.
7. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: In step S4, the inert gas is one or more of nitrogen, helium, neon, argon, krypton, and xenon, and the purity of the inert gas is maintained above 99.9%.
8. The method for preparing a fiber membrane with a high porosity and corrosion-resistant armored structure according to claim 1, characterized in that: The coupling reaction in step S4 is a Sonogashira coupling reaction, the reaction temperature is 40-80° C., and the reaction time is 2-72 hours.
9. A fiber membrane prepared by the method for preparing a fiber membrane with a high-porosity, corrosion-resistant armored structure as described in claim 1.
10. Use of the fiber membrane according to claim 9 in a filter material for simultaneously filtering out ultrafine dust and toxic gases.
Citation Information
Patent Citations
Metal organic framework / polymer nanofiber composite membrane material and preparation method thereof
CN107022899A
Method for preparing TEMPO free radical functionalized hollow conjugated microporous polymer based on SiO2 template and application
CN112159515A
Fiber catalytic membrane based on conjugated microporous polymer as well as preparation method and application of fiber catalytic membrane
CN116180454A
High-porosity self-powered stereocomplex polylactic acid fiber filter membrane and preparation method thereof
CN116712874A
Polylactic acid nanofiber filtering membrane as well as preparation method and application thereof
CN119186276A